Production of 1, 6-hexanediol from tetrahydropyran-2-methanol by dehydration–hydration and hydrogenation. Issue 5 (9th February 2017) - Burt, Samuel P.; Barnett, Kevin J.; McClelland, Daniel J.; Wolf, Patrick; Dumesic, James A.; Huber, George W.; Hermans, Ive
Abstract : In this work we present an alternate method for the conversion of tetrahydropyran-2-methanol (THP2M), a cellulose-derived renewable building block, to 1, 6-hexanediol (1, 6-HDO). Abstract : In this work we present an alternate method for the conversion of tetrahydropyran-2-methanol (THP2M), a cellulose-derived renewable building block, to 1, 6-hexanediol (1, 6-HDO). Our method is composed of three consecutive steps that either use relatively inexpensive catalysts or no catalyst at all. First, THP2M is catalytically dehydrated to 2, 3, 4, 5-tetrahydrooxepine (THO) in up to 40% yield. THO is then hydrated to 2-oxepanol (OXL) and 6-hydroxyhexanal (6HDHX) with a combined yield of 85% in the absence of a catalyst. OXL and 6HDHX are then quantitatively hydrogenated to 1, 6-HDO over a commercially available Ni/C or Ru/C catalyst. Various silicoaluminates were screened for the first acid-catalyzed reaction, and it was found that K-BEA shows the highest THO yield (40% over fresh catalyst, 20% after 25 h on stream). An overall 1, 6-HDO yield of 34% from THP2M was obtained.